A Method for Service Agile Construction - Carvalho, Felipe; Azevedo, Leonardo Guerreiro; Santos, Gleison (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2014)
Service-Oriented Architecture (SOA) and agile methods share common drivers. However, there is a lack of guidelines a SOA team should pursue in order to develop services considering best practices, acceptance tests, distributed teams, contract refactoring, among other issues related to SOA principles and agile practices. This work presents a new method that addresses team concerns and needs aiming at a systematic approach for service development using XP's agile practices and SOA principles. We provide best practices, phases and activities that specifically address XP's core practices and service-oriented best practices. We also provide an example of our proposal in order to demonstrate its applicability.